Pengaruh latihan passing kombinasi terprogram terhadap peningkatan teknik dasar passing bawah pada ekstrakurikuler bola voli putri SMA Negeri 25 Bone - Asriani, Ria; Khalid Rijaluddin; Andi Mutmainna (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The low level of basic underhand passing skills among female volleyball extracurricular students at SMA Negeri 25 Bone indicates the need for a more structured and varied training program. This study aimed to determine the effect of a programmed combination passing training program on improving basic underhand passing skills in volleyball. The study employed a quantitative approach using a One Group Pretest–Posttest Design. The sample consisted of nine female volleyball extracurricular students selected through purposive sampling. Data were collected using an underhand passing accuracy test administered before (pre-test) and after (post-test) the intervention. The treatment consisted of a programmed combination passing training program, including wall passing, partner passing, and target passing exercises conducted over 12 training sessions. Data were analyzed using descriptive statistics and inferential statistics, including normality and homogeneity tests, followed by a paired sample t-test. The results showed that the mean underhand passing score increased from 14.67 in the pre-test to 18.67 in the post-test, with an average improvement of 4.00 points. Hypothesis testing revealed a significance value of 0.000 (p < 0.05), indicating a significant effect of the programmed combination passing training on improving underhand passing skills. It can be concluded that systematic, structured, and repetitive combination passing training effectively improves the basic underhand passing skills of female volleyball extracurricular students at SMA Negeri 25 Bone.